Phosphorus induced changes in food quality enhance porina fitness feeding on Epichloë endophyte free forage grasses - Katrin G. Hewitt; Rainer W. Hofmann; Olivier J. Ball; Sarah C. Finch; Racheal H. Bryant; Alison J. Popay (Scientific Reports)
Abstract The increasing expenses and environmental repercussions associated with phosphorus (P) fertiliser underscore the necessity for precision-managed application methods. These changes affect pastoral systems, where cool-season grasses like perennial ryegrass and meadow fescue form beneficial relationships with Epichloë endophytes. Understanding how fertilisers influence these endophytes, host grasses, and insect pests is crucial, as Epichloë endophytes enhance resistance to some herbivorous insects. This study examined the indirect impact of various P fertiliser regimes on cool-season grasses, which serve as food sources for porina larvae (Wiseana copularis), a significant pasture pest in New Zealand. Endophyte-infected (Epichloë sp. LpTG-3 strain AR37) perennial ryegrass and meadow fescue infected with E. uncinata (strain MaxR (AR1017)), alongside their endophyte-free counterparts were grown in P-enriched soil with varying Olsen P levels (9, 18, 28, and 78 mg/L). Freeze-dried foliage was added to semi-synthetic diets and fed to porina larvae in a no-choice assay. Measurements included diet consumption, porina survival, weight gain. Measurements in foliage included fungal alkaloid concentration, fungal biomass, and plant nutrient levels. Endophyte infection of AR37 and MaxR significantly reduced porina diet consumption, larval weight gain and survival irrespective of soil Olsen P levels to the plant. Loline alkaloid concentration in MaxR-infected herbage increased with increasing soil Olsen P levels while fungal mass remained unchanged. In endophyte-free grasses, porina larvae significantly increased their diet consumption, weight gain and survival as the Olsen P level available to the host plant increased. While endophyte strains AR37 and MaxR continue to protect their hosts under different Olsen P regimes, these results suggest that the improved performance of porina on endophyte-free plants is largely driven by P-induced changes in food quality. Here, we discuss the implications of porina damage in New Zealand pastures in the context of decreasing P availability.